Development Of Novel Processed Tilapia Products For The Group Of Female Fish Farmers In The Village Of Ranu Klakah Lumajang - Maimunah, Yunita (Journal of Innovation and Applied Technology, 2024)
Ranu Klakah, a volcanic lake in East Java, is explored as a site for tilapia cultivation. Upwelling, the process of nutrient-rich deep water rising to the surface due to wind-induced currents, is examined for its effects on water quality and fish productivity. The activity focuses on the impact of upwelling on tilapia, including reduced water quality, scarcity of natural fish food, physiological stress, disease susceptibility, and decreased fish production. To address the challenges posed by upwelling, it suggests processing tilapia into value-added products, like fish nuggets and skin chips, to enhance market value. Community service activities involving training for making these processed fish products are described, aiming to empower women in the fish farming sector and improve family income. We conclude with insights into the potential benefits of these activities and their positive impact on the local community